2013
DOI: 10.12659/msmbr.883956
|View full text |Cite
|
Sign up to set email alerts
|

New patterns of the growing L3 vertebra and its 3 ossification centers in human fetuses – a CT, digital, and statistical study

Abstract: BackgroundThis study describes reference data for L3 vertebra and its 3 ossification centers at varying gestational ages.Material/MethodsUsing CT, digital-image analysis and statistics, the growth of L3 vertebra and its 3 ossification centers in 55 spontaneously aborted human fetuses aged 17–30 weeks was examined.ResultsNeither sex nor right-left significant differences were found. The height and transverse and sagittal diameters of the L3 vertebral body increased logarithmically. Its cross-sectional area foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
1
18
1
3
Order By: Relevance
“…Vignolo et al [26] reported that ossification started earlier in female fetuses, thus male fetuses were more difficult to assess in this respect. The present paper and our previous findings [4, 5, 2224] have not confirmed any sex differences in ossification of the spine. Therefore, in the present study both numerical data and statistical analysis are presented aggregately without taking sex into account.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Vignolo et al [26] reported that ossification started earlier in female fetuses, thus male fetuses were more difficult to assess in this respect. The present paper and our previous findings [4, 5, 2224] have not confirmed any sex differences in ossification of the spine. Therefore, in the present study both numerical data and statistical analysis are presented aggregately without taking sex into account.…”
Section: Discussioncontrasting
confidence: 55%
“…As reported in the medical literature, the vertebral body ossification centers revealed a natural logarithmic increase in both transverse and sagittal diameters. This was substantiated by Baumgart et al [5] in relation to vertebra C4 ( y  = −8.836 + 3.708 × ln(age) and y  = −7.748 + 3.240 × ln(age), respectively) and by Szpinda et al [23, 24] in relation to both vertebrae T6 ( y  = −14.784 + 6.115 × ln(age) and y  = −12.065 + 5.019 × ln(age), respectively) and L3 ( y  = −27.610 + 10.341 × ln(age) and y  = −13.858 + 5.636 × ln(age), respectively).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations